Analisis faktor-faktor penyebab Anak menjadi Attention Defict Hyperactive Disorder di SDN Teluk Pucung 01 Kota Bekasi - A Awiria; D Dariyanto (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2020)
The purpose of this study was to analyze the factors that cause children to become Attention Defict Hyperactive Diserder (ADHD) in elementary schools. This research was conducted at SDN Teluk Pucung 01 Bekasi City, with the research subjects 2 students of SDN Teluk Pucung 01 Elementary School Bekasi City. This research method is a qualitative method with a case study approach model. The research data were obtained using research instruments in the form of interviews, observation, and documentation. Then analyzed using Miles Huberman's theory with the stages of data reduction, data presentation and drawing conclusions and verification. The results showed that genetics, the diet of parents during pregnancy, psychosocial factors, namely poor parenting management, and environmental factors such as lead poisoning, food addiction, allergic reactions, and being in a smoking environment are the main factors that cause children to become Attention Defict. Hyperactive Diserder (ADHD)